The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1113/jphysiol.2013.255836
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Kv4 protein by the accessory K+ channel interacting protein 2 (KChIP2) subunit is required for the generation of native myocardial fast transient outward K+ currents

Abstract: Key points• The cytosolic K + channel accessory subunit, K + channel interacting protein 2 (KChIP2), was previously suggested to be critical in the generation of cardiac fast transient outward current (I to,f ) channels.• The experiments presented here revealed the novel finding that targeted deletion of KChIP2 results in the complete loss of the Kv4.2 protein, although Kcnd2 (Kv4.2) transcript expression is not decreased in KChIP2 −/− ventricles.• In contrast, the slow transient outward current, I to,s , is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 49 publications
(123 reference statements)
11
48
3
Order By: Relevance
“…The involvement of NF-B in ␤-AR-mediated effects on I to,f is consistent with previous studies showing that KChIP2 facili- tates insertion of I to,f channels into cell membranes (30) while also limiting channel degradation (31). Importantly, NF-B inhibition had no measureable effects on I to,f densities in the absence of ␤-AR stimulation, despite causing elevations of KChIP2 mRNA levels under these conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The involvement of NF-B in ␤-AR-mediated effects on I to,f is consistent with previous studies showing that KChIP2 facili- tates insertion of I to,f channels into cell membranes (30) while also limiting channel degradation (31). Importantly, NF-B inhibition had no measureable effects on I to,f densities in the absence of ␤-AR stimulation, despite causing elevations of KChIP2 mRNA levels under these conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that complete loss of KChIP2 in mouse ventricular myocardium results in elimination of I to,f 29 . In Notch GOF mice, KChIP2 protein levels are reduced by about 50% (Figure 3D).…”
Section: Resultsmentioning
confidence: 96%
“…In Notch GOF mice, KChIP2 protein levels are reduced by about 50% (Figure 3D). To explore the hypothesis that the reduction of KChIP2 in Notch GOF is sufficient to attenuate I to,f , whole-cell Kv current recordings were obtained from LV myocytes isolated from KChIP2 +/− mice lacking one copy of Kcnip2 29 . Analyses of the voltage-clamp data obtained in these experiments revealed that mean ± SEM I K,peak ( P = 0.018) and I to,f ( P = 0.0026) densities were significantly lower in KChIP2 +/− LV myocytes, than in control LV myocytes (Online Figure IV; Table 2), whereas I K,slow , I ss and I K1 densities in KChIP2 +/− and control LV myocytes were not significantly different (Online Figure IV; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, adenoviral-mediated overexpression of KChIP2 was unable to restore I to,f density in cultured adult mouse KChIP2(−/−) myocytes (Foeger et al, 2013) or to increase it in cultured adult canine endocardial myocytes (Rosati and McKinnon, unpublished). The apparent failure of KChIP2 to rescue expression of I to,f in adult cultured myocytes may reflect a technical issue, since transcription of multiple ion channel subunit genes, including Kv4.2, can be markedly down-regulated in these cells when placed in culture (Hershman and Levitan, 1998), Rosati and McKinnon, unpublished).…”
Section: Molecular Basis Of Ito and Its Transmural Gradient Of Expresmentioning
confidence: 99%